A clinical distance measure for evaluating treatment plan quality difference with Pareto fronts in radiotherapy. (July 2017) - Petersson, Kristoffer; Kyroudi, Archonteia; Bourhis, Jean; Ceberg, Crister; Knöös, Tommy; Bochud, François; Moeckli, Raphaël
Abstract: We present a clinical distance measure for Pareto front evaluation studies in radiotherapy, which we show strongly correlates (r = 0.74 and 0.90) with clinical plan quality evaluation. For five prostate cases, sub-optimal treatment plans located at a clinical distance value of >0.32 (0.28–0.35) from fronts of Pareto optimal plans, were assessed to be of lower plan quality by our (12) observers (p < .05). In conclusion, the clinical distance measure can be used to determine if the difference between a front and a given plan (or between different fronts) corresponds to a clinically significant plan quality difference.